2015
DOI: 10.1111/omi.12106
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus gordoniiDL1 adhesin SspB V‐region mediates coaggregation via receptor polysaccharide of Actinomyces oris T14V

Abstract: Streptococcus gordonii SspA and SspB proteins, members of the antigen I/II (AgI/II) family of Streptococcus adhesins, mediate adherence to cysteine-rich scavenger glycoprotein gp340 and cells of other oral microbial species. In this article we investigated further the mechanism of coaggregation between S. gordonii DL1 and Actinomyces oris T14V. Previous mutational analysis of S. gordonii suggested that SspB was necessary for coaggregation with A. oris T14V. We have confirmed this by showing that Lactococcus la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…gordonii adhesin, SspB, is directly involved in interacting with the Mfa1 surface protein of Porphyromonas gingivalis to promote P . gingivalis biofilm formation, and also mediates binding to an Actinomyces oris -derived polysaccharide [3133]. However, unlike previous studies that demonstrate adhesin-specific interactions between bacteria that are generally specific to the oral cavity, our study highlights a unique association between an oral bacterial adhesin and a polysaccharide produced by a traditionally non-oral bacterium.…”
Section: Discussionmentioning
confidence: 60%
“…gordonii adhesin, SspB, is directly involved in interacting with the Mfa1 surface protein of Porphyromonas gingivalis to promote P . gingivalis biofilm formation, and also mediates binding to an Actinomyces oris -derived polysaccharide [3133]. However, unlike previous studies that demonstrate adhesin-specific interactions between bacteria that are generally specific to the oral cavity, our study highlights a unique association between an oral bacterial adhesin and a polysaccharide produced by a traditionally non-oral bacterium.…”
Section: Discussionmentioning
confidence: 60%
“…It is possible that there are additional coaggregation mechanisms between A. oris T14V and S. oralis 34 that are secondary to the fimbriae-RPS interaction. For example, we have recently shown that the Streptococcus gordonii SspB (antigen I/II-family) protein binds to a polysaccharide receptor present on A. oris T14V (Back et al, 2015). Streptococcus oralis 34 also carries an antigen I/II protein-encoding gene, and so the S. oralis antigen I/II protein might act similarly.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, strong coaggregation is mediated by interactions between one type of adhesin and a complementary receptor. For example, S. gordonii DL1 SspB is necessary and sufficient for binding to an Actinomyces oris MG1 cell surface carbohydrate and mediating coaggregation . Other coaggregation interactions involve multiple proteins and/or carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…For example, S. gordonii DL1 SspB is necessary and sufficient for binding to an Actinomyces oris MG1 cell surface carbohydrate and mediating coaggregation. 7,8 Other coaggregation interactions involve multiple proteins and/or carbohydrates. Recent evidence indicates that coaggregation between Fusobacterium nucleatum and S. gordonii involves at least three F. nucleatum outer membrane proteins: two arginine-inhibitable adhesins, RadD and CmpA, and an accessory protein Aid1 that facilitates RadD-mediated adhesion.…”
mentioning
confidence: 99%